Samuel said, *“If yesterday was tomorrow, today would be Friday.”*

What day did Samuel say this?

**Sunday** or **Wednesday** depends on how you interpret this sentence, *“If yesterday was tomorrow.”*

**Let:**

YES = Real Yesterday

YES’ = Imaginary Yesterday

TOD = Real Today

TOD’ = Imaginary Today

TOM = Real Tomorrow

TOM’ = Imaginary Tomorrow

**Assumption I:**

**1.** Yesterday in the sentence is the **Real Yesterday (YES)**.

**2.** Tomorrow in the sentence is the **Imaginary Tomorrow (TOM’)**.

**3.** Today in the sentence is the **Imaginary Today (TOD’)**.

**Thus:**

**YES = TOM’** *(i)*

**TOD’ = Friday** *(ii)*

**TOM’ = TOD’ + 1** *(iii)*

**TOD = YES + 1** *(iv)*

**Using equation (i) and (iii):**

YES = TOM’

YES =

**(TOD’ + 1)**

**YES = TOD’ + 1**

*(v)*

**Using equation (iv) and (v):**

TOD = YES + 1

TOD =

**(TOD’ + 1)**+ 1

**TOD = TOD’ + 2**

*(vi)*

**Using equation (ii) and (vi):**

TOD = TOD’ + 2

TOD =

**Friday**+ 2

**TOD = Sunday**

**Assumption II:**

**1.** Yesterday in the sentence is the **Imaginary Yesterday (YES’)**.

**2.** Tomorrow in the sentence is the **Real Tomorrow (TOM)**.

**3.** Today in the sentence is the **Imaginary Today (TOD’)**.

**Thus:**

YES’ = TOM

**TOM = YES’** *(i)*

**TOD’ = Friday** *(ii)*

**YES’ = TOD’ – 1** *(iii)*

**TOD = TOM – 1** *(iv)*

**Using equation (i) and (iii):**

TOM = YES’

TOM =

**(TOD’ – 1)**

**TOM = TOD’ – 1**

*(v)*

**Using equation (iv) and (v):**

TOD = TOM – 1

TOD =

**(TOD’ – 1)**– 1

**TOD = TOD’ – 2**

*(vi)*

**Using equation (ii) and (vi):**

TOD = TOD’ – 2

TOD =

**Friday**– 2

**TOD = Wednesday**

Q.E.D.